Exopolysaccharides production and characterization of Fusarium mangieferae from mango (Mangifera indica) with some commercial potential applications - Mittholiya, Shivangi; Meena, Bhanu Raj; Chittora, Deepali; Yadav, Jyoti; Jain, Tripta; Sharma, Kanika (Journal of Postharvest Technology, 2022)
Nine common fungi were isolated from different fruits plant such as amla (Phyllanthus emblica), banana (Musa acuminate) and mango (Mangifera  indica). The most promising fungus producing exopolysaccharide (EPS) was Fusarium mangieferae which was identified according to microscopic  morphological features and confirmed by IARI, Delhi. Three main spectroscopic analyses (FTIR, TLC and GC-MS) were employed to characterize the  EPS extracted from marine-derived Fusarium mangieferae . The monosaccharide composition of EPS determined by TLC indicates it is a  homopolysaccharide composed of glucose. The FT-IR analysis proves the presence of biologically important functional groups and alpha glycosidic  linkage between individual glycosyl residues. The GC-MS chromatography showed that the EPS consist of one peak of glucose hence Fusarium  mangieferae EPS is homopolysaccahride. EPS of Fusarium mangieferae showed antibacterial activity against Klebsiella aerogenes is 29 mm and  also have emulsification and bioflocculation activity.
Keywords: Exopolysaccharide; emulsification; bioflocculation,; postharvest